Homens e mulheres de "palavra": diálogo e educação popular - Flávio Henrique Albert Brayner (Universidade do Minho, 2009)
The idea - and determined practice - of "dialogue" forms such a substantial part of Popular Education that this education is defined as a "dialogical pedagogy". In other words, the means defines the pedagogy! This occurs in such a natural way that we forget to inquire the conceptual basis of such a notion. In this article, we try to show that if this notion has the finality of establishing or facilitating inter-subjective consensus, then the notion itself isn¿t consensual. To analyze different semantic profiles we recur to four well-known authors - Hannah Arendt, Martin Buber, Jürgen Habermas and, of course, Paulo Freire - to "present" concepts on dialogue. We found not only great differences among these authors, but also that in each resides a declared or subconscious intention of saving mankind through the "word", whether via its mystic or secular virtues. The article concludes that the commonly accepted relation between dialogue and liberation/emancipation seems to have lost its potential, inviting us to be more modest in our pedagogical intentions and more precise in our vocabulary.